1990
DOI: 10.1128/iai.58.1.163-168.1990
|View full text |Cite
|
Sign up to set email alerts
|

Cellular coaggregation of oral Streptococcus milleri with actinomyces

Abstract: Oral isolates of Streptococcus milleri were examined for their ability to coaggregate with actinomyces. Of the 68 S. mileri strains tested, including 3 reference strains, 40 strains coaggregated with Actinomyces naeslundii WVU45 (actinomyces coaggregation group B) and 36 strains coaggregated with Actinomyces viscosus T14V (actinomyces coaggregation group A). AU S. milleri strains of serotypes b (4 strains), e (2 strains), and f ( 24strains) coaggregated with both of the actinomyces. The coaggregation reactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
11
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…Recently, we have isolated many strains of serotypes other than b, e, and f/F from the mouths of children (16). By employing these strains, the present studies confirm and extend the previous findings regarding the coaggregation of S. milleri with actinomyces (5,14) which is not inhibited by lactose. Certain oral S. milleri strains exhibit coaggregation which is inhibited by lactose.…”
supporting
confidence: 89%
See 3 more Smart Citations
“…Recently, we have isolated many strains of serotypes other than b, e, and f/F from the mouths of children (16). By employing these strains, the present studies confirm and extend the previous findings regarding the coaggregation of S. milleri with actinomyces (5,14) which is not inhibited by lactose. Certain oral S. milleri strains exhibit coaggregation which is inhibited by lactose.…”
supporting
confidence: 89%
“…Our previous studies demonstrated that large numbers of Streptococcus milleri isolates from human mouths (15,17) coaggregate with cells of actinomyces coaggregation groups A and B and that all belong to serotype b, e, or f/F (5). The coaggregation reactions of these S. milleri strains are not inhibited by lactose and are mediated by streptococcal adhesins and actinomyces carbohydrate receptors, suggesting that these strains belong to streptococcus coaggregation group 2.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…There are several approaches to disaggregating cell clumps, including antibodies, antibiotics, chaotropes, enzymes and low molecular mass saccharides complementary to lectins. Experiments performed some years ago by Cisar et al [7], McIntire et al [8], Kolenbrander et al [9] and Eifuku et al [10] suggest that adhesins of Actinomyces spp. may be inhibited by chelating agents, such as EDTA.…”
Section: Introductionmentioning
confidence: 99%